Implementasi Metode Pembelajaran Problem-Solving Berbantuan Video Tutorial pada Mata Pelajaran Dasar Ketenagalistrikan - Karta, Muhammad Fauzi; Aswardi, Aswardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This research aims to increase students' enthusiasm for learning and happiness through the implementation of the Problem-Solving learning method with video tutorials on basic Electricity learning objects at SMKN 1 Guguk. The low student learning outcomes, which can be seen from several students achieving scores below the Learning Goal Achievement Criteria (KKTP), are the background for this research. The method used is a type of quantitative research with a one-group pretest-posttest quasi-experimental design method. The initial stage involves taking a pretest to evaluate students' initial abilities, followed by treatment using the Problem-Solving learning method with video tutorials. The final evaluation is carried out through a posttest to show an increase in student learning outcomes after implementing the method. The results showed a significant increase in pretest-posttest scores. There is also an increase in the level of accuracy of learning, with the majority of students achieving the expected level. The advantages and impact of this method show that the implementation of the Problem-Solving learning method with video tutorials is effective in improving student learning outcomes in basic subjects taught at SMKN 1 Guguk.